2022
DOI: 10.1002/ael2.20068
|View full text |Cite
|
Sign up to set email alerts
|

Combining diffusive gradients in thin‐films (DGT) and 31P NMR spectroscopy to determine phosphorus species in soil

Abstract: The diffusive gradients in thin-films (DGT) technique shows in many publications a superior correlation to the amount of plant-available phosphorus (P) in soil. However, this technique cannot give information on the plant-available P species in soil. Therefore, we combined DGT with solution 31 P nuclear magnetic resonance (NMR) spectroscopy. This was achieved by using a modified DGT device in which the diffusive layer had a larger pore size, the binding layer incorporated an adsorption material with a higher c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 25 publications
0
1
0
Order By: Relevance
“…It was found that plant-available P was obtained after 2 weeks of incubation. In a previous study, Vogel et al (2021) combined DGT and 13 P NMR to determine P species in soil. This combination allowed the authors to identify organic P species in solutions.…”
Section: Dgt Applications To Nutrient Labile Fractions In Soilmentioning
confidence: 99%
“…It was found that plant-available P was obtained after 2 weeks of incubation. In a previous study, Vogel et al (2021) combined DGT and 13 P NMR to determine P species in soil. This combination allowed the authors to identify organic P species in solutions.…”
Section: Dgt Applications To Nutrient Labile Fractions In Soilmentioning
confidence: 99%